Jacques Maritain and the Jewish Question: Theology, Identity and Politics - Ventresca, Robert A. (Studies in Christian-Jewish Relations, 2011)
This article calls for a reconsideration of Jacques Maritain’s philosophical and theological reflections on the ‘Jewish Question’, on anti-Semitism and, more broadly, on Jewish-Christian relations in modern history. The article follows two broad lines of enquiry. First, it sketches a general outline of Maritain’s arguments against Catholic-Christian anti-Semitism, and his proposals for workable solutions to what he identified as the ‘Jewish problem’ in European life. Second, the article considers the practical value of Maritain’s visions of a ‘new Christendom’, that is, of a new political regime based on Gospel-values and thus recognizing the complete civic equality, political and religious freedoms of European Jews. The article concludes that all of Maritain’s thought on the Jewish question must be read through the lens of his Christian eschatological view.